Detection of iron deficiency anaemia in anaemia of chronic disease patients in HUSM : a preliminary case control study - Ramli, Marini (2006)
Detecting iron deficiency anaemia (IDA) in anaemia of chronic disease (ACD) patients is not easy, as the conventional laboratory indices of iron status are often influenced by acute phase responses. The aim of the study is to determine the prevalence of iron deficiency in ACD patients using various haematological tests and to compare with the normal control. Sixty ACD patients were purposively recruited while 25 controls were healthy volunteers among the HUSM staffs. Both groups had to fulfill their inclusion and exclusion criteria before they were tested to determine the iron status. Investigations for iron status consisted of full blood picture with other haematological indices, serum ferritin, soluble transferrin receptor (sTfR) and Transferrin receptor-ferritin index (TfR-F index). Results showed that none of the controls were having iron deficiency anaemia. Coexisting IDA in ACD group were detected 20% by sTfR, 16.7% by TfR-F index and none using serum ferritin. There were significantly lower mean corpuscular volume (MCV) and serum ferritin but higher for red cell distribution width (RDW) and sTfR. in ACD group compared to the normal controls (P<O.OOl) Comparing IDA cases and the non-IDA cases in the ACD group, there were significantly lower mean corpuscular volume (MCV),mean cell haemoglobin concentration (MCHC) and serum ferritin but higher for red cell distribution width (RDW) and sTtR (P<O.OOl), The findings above pointed towards "IDA-like" profile and support the possibility of coexisting iron deficiency anaemia. The mean sTtR level was not significantly different between males and females in the control group. However, a weak correlation was noted between age and sTfR levels. In conclusion, a proportion of ACD patients had coexisting IDA and knowing this coexistence will be beneficial, as it will assist in better management of these patients.